2015
DOI: 10.1080/00218464.2015.1046596
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Formaldehyde Emission from Particleboard by Phenolated Kraft Lignin

Abstract: The aim of this study was the reduction of formaldehyde emission from particleboard by phenolated Kraft Lignin. For this purpose, the lignin was extracted from black liquor and then modified by phenolation. During the UF resin synthesis different proportions of unmodified and phenolated Kraft lignins (10, 15 and 20%) were added at pH=7 instead of the second urea. Physicochemical properties and structural changes of resins so prepared, as well as the internal bond (IB) strength and formaldehyde emission associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…The slightly lower formaldehyde contents of the PBs produced with resins UF‐10LH‐d, UF‐10L‐a, UF‐10LH‐a, and UF‐20LH‐a, may indicate that TSSL/TSSLH may act as a formaldehyde scavenger. The capacity of technical lignins to work as formaldehyde scavengers has been reported before . This is explained, in part, by the reaction of sulfite ions, present in TSSL, with formaldehyde, producing a formaldehyde‐sulfite adduct, hydroxymethanesulfonate .…”
Section: Methodsmentioning
confidence: 64%
See 1 more Smart Citation
“…The slightly lower formaldehyde contents of the PBs produced with resins UF‐10LH‐d, UF‐10L‐a, UF‐10LH‐a, and UF‐20LH‐a, may indicate that TSSL/TSSLH may act as a formaldehyde scavenger. The capacity of technical lignins to work as formaldehyde scavengers has been reported before . This is explained, in part, by the reaction of sulfite ions, present in TSSL, with formaldehyde, producing a formaldehyde‐sulfite adduct, hydroxymethanesulfonate .…”
Section: Methodsmentioning
confidence: 64%
“…In recently published works, technical lignins, previously hydroxymethylated or phenolated, were used to replace part of the urea (15–30%), and were introduced during the resin synthesis . In general, the produced resins presented lowered free formaldehyde levels and the resulting wood composites verified the standard performance requirements.…”
Section: Introductionmentioning
confidence: 98%
“…Conversely, Younesi-Kordkheili et al reported diminishing formaldehyde emission in urea-formaldehyde resin modified with phenolated lignin. Interestingly, even 10% modified lignin incorporation into a resin can lead to a significant decrease in free formaldehyde content (0.26%) compared to the control (0.40%) [35]. The foregoing examples are summarized in Table 2.…”
Section: Lignin In Phenol-formaldehyde (Pf) Resinsmentioning
confidence: 99%
“…In the same study, further improvement of physical and mechanical properties was obtained by adding nanoclay to the LUG resin. Lignin was modified by phenol and used in UF resins [110]. It was demonstrated that the formaldehyde emission from wood panels, bonded with modified lignin-UF resin, was lower compared with commercial UF adhesives.…”
Section: Ligninmentioning
confidence: 99%